(untitled) (Acta Scientiarum. Technology, 2021)
Blood glucose is conventionally determined by the level of sugar present in our blood. Lesser known to the public that antioxidants in our body are also said to influence the level of blood glucose. Glutathione (GSH) as the main antioxidant parameter in our body helps in reducing the production of oxidative stress caused by a high blood glucose level. Particularly in women, high antioxidant activities are reported due to the presence of oestrogen hormone. However, in Malaysia limited study was done on the significance of GSH in influencing the blood glucose level. Thus, this study focuses on finding the significance of GSH and some other health predictors in affecting the blood glucose level of women volunteers. This study was carried out on 118 Malaysian women volunteers and blood samples were collected for GSH analysis and blood glucose. All data were trained and tested for the development of prediction models in classifying the blood glucose into normal and abnormal levels. The model construction is using three different classifiers: namely logistic regression, k-nearest neighbour classifier and decision tree. Five predictors that were used are GSH, weight, body mass index (BMI), waist-hip ratio (WHR) and groups (oral supplementation dosage). Results showed all predictors are significantly correlated with the blood glucose level at p < 0.10. The model with a combination of GSH, BMI, WHR, weight and supplementation dosage (groups) as predictors gave the best performance. The k-nearest neighbour classifier model displays the best accuracy (84.7%) in predicting the normal and abnormal level of blood glucose. This finding shows that by altering the amount of GSH via oral supplementation and other significant predictors in women, there are chances to modify the blood glucose level from abnormal to normal